2011 IEEE Trondheim PowerTech 2011
DOI: 10.1109/ptc.2011.6019454
|View full text |Cite
|
Sign up to set email alerts
|

Smart grid simulation using small-scale pilot installations. - experimental investigation of a centrally-controlled microgrid

Abstract: Two smart-grid topologies are analyzed in this paper. The first one has two main differences from the traditional grid, a dc-bus and a smart integration module (SIM), which interconnects the dc-with the ac-bus. The second topology has only one difference from the traditional grid, a special control unit (SCU), which is attached to each device before connecting to the grid. The first topology has been implemented in a small-scale installation. This small-scale pilot installation is described and experimental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 5 publications
0
13
0
4
Order By: Relevance
“…The last module is integrated into software that runs on a microgrid-dedicated PC. This topology is implemented at the facilities of the Technological Educational Institute of Western Macedonia [1], [9], [10].…”
Section: Description Of the Microgrid Topologymentioning
confidence: 99%
See 2 more Smart Citations
“…The last module is integrated into software that runs on a microgrid-dedicated PC. This topology is implemented at the facilities of the Technological Educational Institute of Western Macedonia [1], [9], [10].…”
Section: Description Of the Microgrid Topologymentioning
confidence: 99%
“…This parameter is taken into account, since tests showed that switching on-off large loads could lead to great discharging currents, which in their turn are misleading indications for the correct estimation of the SoC by the linear method. The wrong SoC estimation can lead to unnecessary load rejection and thus decreased power supply reliability [9], [10]. Thus, the term "pseudo State of Charge" (pseudo-SoC) is defined as the SoC that is assigned to the batteries on purpose, when great discharging currents appear in a 2-minutes period and the (V mean-2 , I mean-2 ) point skips one of the above SoC areas, i.e.…”
Section: A Energy Storage Management Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…At the first topology [6], [7], a dc-bus is added, for connection to dc loads, dc-generators, battery banks and energy storage in general. Additionally, a new building block technology called smart integration module (SIM) is needed, as interconnection between the dc and the ac bus.…”
Section: Analytical Description Of the First Smart Grid Topology mentioning
confidence: 99%
“…In [6], two topologies for the smart distribution grid are analyzed, the infrastructure for implementing the first topology in experimental scale is described and the first experimental results are presented. The aim of this paper is to present analytically the developed infrastructure for implementing the second topology in experimental scale and present more experimental results by the microgrids.…”
Section: Introductionmentioning
confidence: 99%